2015
DOI: 10.1186/s12889-015-1584-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness and cost-effectiveness of peer education and peer support in prisons

Abstract: BackgroundPrisoners experience significantly worse health than the general population. This review examines the effectiveness and cost-effectiveness of peer interventions in prison settings.MethodsA mixed methods systematic review of effectiveness and cost-effectiveness studies, including qualitative and quantitative synthesis was conducted. In addition to grey literature identified and searches of websites, nineteen electronic databases were searched from 1985 to 2012.Study selection criteria were:Population:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
130
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 65 publications
4
130
0
11
Order By: Relevance
“…Peer support processes continue to be a popular intervention within the prison setting, and recent evidence derived from a systematic review has demonstrated the value of this in relation to a spectrum of health and social issues (Bagnall et al, 2015). Our analysis suggested that only 41% of prisoners were utilising peer support approaches for health and well-being.…”
Section: Discussionmentioning
confidence: 79%
“…Peer support processes continue to be a popular intervention within the prison setting, and recent evidence derived from a systematic review has demonstrated the value of this in relation to a spectrum of health and social issues (Bagnall et al, 2015). Our analysis suggested that only 41% of prisoners were utilising peer support approaches for health and well-being.…”
Section: Discussionmentioning
confidence: 79%
“…It is apparent that peer interpreters in prison may take on informal roles that are in keeping with peer support workers. Prison peer support programmes are an emerging approach to bridge health service gaps; the research suggests benefits exist, but evidence is generally limited . These programmes utilize prisoners who are formally trained and employed in either paid or unpaid roles and include peer support and health education activities .…”
Section: Discussionmentioning
confidence: 99%
“…Prison peer support programmes are an emerging approach to bridge health service gaps; the research suggests benefits exist, but evidence is generally limited . These programmes utilize prisoners who are formally trained and employed in either paid or unpaid roles and include peer support and health education activities . They have the potential to reduce barriers to health care and empower CALD women through advocacy and support, while promoting cohesion within the prison community and supporting its rehabilitative function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that a wide range of peer support schemes and interventions are undertaken in UK prison settings (Fletcher and Batty, 2012, South et al, 2014, Bagnall et al, 2015 Majesty's Inspectorate of Prisons HMIP, 2016), and that specific prisoner support roles are carried out in a range of informal and formal ways, (Stewart, 2011, Loeb, 2013. It is known that schemes focusing on developing prisoner peer workers are well developed in the United States of America (USA), particularly in relation to the escalating cost of caring for prisoners with dementia (Belluck, 2012) and prisoners nearing the end of their life (Stone et al, 2011).…”
mentioning
confidence: 99%